KEWENANGAN PENGAWAS KETENAGAKERJAAN TERHADAP PEKERJA ANAK DI KABUPATEN LOMBOK TIMUR - Sakaki Sakaki; Suyadi Suyadi; Firzhal Arzhi Jiwantara (Bajang Institute, 2022)
This research is a juridical-empirical legal research, the approach used is a statutory approach and a conceptual approach. The analytical method used is descriptive analytical method. Supervision by Supervision Labor inspection is an activity carried out by the government to ensure that the provisions of laws and regulations. concerning Manpower are implemented for the relationship between employers and workers and are adhered to by all parties. Supervision is carried out in an effort to oversee labor laws. Factors that support labor inspection of child labor in East Lombok Regency are, Willingness to Enter the Company, Conducting counseling, supporting facilities and facilities. Inhibiting factors are supervisory staff, supervisors cannot be investigated directly with company management, supervisory employees may not take direct action (not unchecked), PPNS Number of employees conducting investigations, insufficient time, limited labor inspectors